The role of assisted manipulation in cognitive development (2012)
Objective: Motor experience plays a central role in cognitive development. Assistive technologies can thus provide augmentative manipulation for children with motor disabilities. This paper explores the use of robots to this end. Method: A revision of studies conducted with typicallydeveloping children and children with disabilities regarding the use of robots is presented. This revision provides a description of the cognitive skills required and revealed by the child when using a robot. Opportunities for participation and exploration were identified and further research is discussed. Results: Robots provide insight into the cognitive skills of children with motor disabilities. Robots also provide means for independent exploration and participation in learning and play activities. Integration of augmentative manipulation and communication increases interest and participation of children with disabilities. Conclusion: Children with disabilities can use augmentative manipulation systems to independently explore and interact with their environment. Children can use robots as tools providing them with opportunities to reveal and further develop their cognitive skills. Alternative access methods can increase access for children with severe motor disabilities.